Between a Rock and a Hard Place: Free Trade, Tariffs and the US Labour Movement - Vincenzo Maccarrone; Francesco Sabato Massimo; Angelo Moro (Global Labour Journal)
Donald Trump’s tariff war, which has focused on cars as one of the main targets, has placed unions, and in particular the United Auto Workers (UAW), the main auto industry union in the US, in a complicated strategic position.